Stratal variations in Philippine fertility differentials, 1973-1977 - Villamejor, Maria Fe S. 1958-
This is a study of the stratal variations and correlates of recent fertility in the Philippines. Stratum is defined jointly by the region and type of place of residence of the study women and includes the seven strata identified in the 1978 Republic of the Philippines Fertility Survey (RPFS), namely, Metro-Manila, Urban Luzon, Urban Visayas, Urban Mindanao, Rural Luzon, Rural Visayas, and Rural Mindanao. The study aims to examine and explain the stratal socio-economic, cultural and demographic differentials and determinants of recent fertility of some 7,238 continuously married women for at least five years preceding the RPFS date. More specifically, it aims to complete the following objectives by stratum: 1) compare and analyze regional and urban-rural variations in Philippine fertility differentials; 2) differentiate subgroups with high and low fertility; and 3) identify the major determinants of recent fertility of Filipino women aged 15-49 years in 1978. The study works within a multivariate framework and uses a derivation of Freedman's Overview of the Fertility Process to conceptually present the theoretical links among its eleven predictors and fertility. Procedurally, it starts with a univariate description of the entire sample and each of the stratum subsamples in terms of each of the control, proximate and predictor variables. It then describes and analyzes the nature and strength of the relationship between the demographic controls and the predictor variables in each stratum. Later, it provides a description and analysis of the nature and strength of association and interrelationship among its explanatory variables. It then carries out a comparative bi-variate analysis of the differentials in stratal recent fertility in terms of each of the eleven selected predictors of fertility. Finally, it assesses the magnitude and significance of stratal fertility variations in the country using the technique of multiple dummy regression. As a whole, the analyses here stress the influences upon recent fertility as indexed by the number of live births in the past five years, of the age of the woman at survey date. They also demonstrate that sratum per se was not a very important predictor or recent fertility. Furthermore, they show that the eleven predictors selected for this study failed to account for a modest part of the stratal variations in recent fertility since they only contributed about 5.3 percent of the total variation. More particularly, the data indicate that with respect to fertility differentials, differences by stratum, education (both of the husband and wife), occupation and age at first marriage were very distinct and clear as to make possible the drawing of positive conclusions regarding their relationship with recent fertility . The other group differentials, on the other hand, exhibited no more than slight correlation with fertility. In addition, except for breastfeeding and contraceptive use, all the fertility differentials presented here had observations consistent with theory, as well as with past and other contemporary observations in the country and elsewhere. On the basis of these differentials, our findings indicate that the following were the high-priority groups for population/family planning programs: intermediate educated women in nuclear families: Catholic; married to high school blue collar workers in enterprises owned by the family; first married at ages 15-17 years; non-migrants; breastfeeders and users of contraception, these high priority groups do not deviate with the universally accepted high fertility subgroups. They do not, however, present a highly conclusive delineation of high and low fertility subgroups because as earlier found, only four or five fertility differentials by stratum were significant. The study reveals that only little might be gained by tailoring population policies and program strategies to the varying marital and recent fertility situations in the urban and rural regions. The special efforts required in developing and managing such strategies (and the cost that would be incurred) would be too great in relation to the benefit that would be expected. In addition, the study indicates that not much could be done by population/family planning programs to improve stratal fertility situations in the country because in addition to the small percentage of variation explained by all our predictors, the major determinant identified here (age of woman), as well as the other significant predictors of recent fertility (age at first marriage and education), are beyond the control of these programs. Greater and more effective linkages and integration with other development programs may be done with our population programs. But there is not much assurance that such may increase the contribution of our programs to recent stratal fertility change.